Game-based learning to teach Higher Order thinking in Rural Schools - Case studies in Sarawak Borneo - Fitri Suraya, Binti Mohamad Hapni Joblie; Morini, Luca; Jacey Lynn, Minoi; Sylvester Wielding, Anak Jussem (University of Roma, 2019)
This action research utilised game-based learning principles in rural schools in Sarawak. Game design thinking was proposed as a pedagogical approach to guide teachers to address Higher Order thinking skills in subjects they teach, a requirement in the current national curriculum. Due to the lack of resources, facilities and training commonly faced by rural schools, the initiative was necessary to measure the feasibility of the approach for learning. The study also observed the similarities and differences in local cultural protocols as they differ by location, and adjustments were made to the presentation of Game Design thinking to accommodate community expectations and support. The study proposes a CreativeCulture model, an instructional approach which accommodates inclusive needs of indigenous communities in Sarawak, both within and beyond their local schools.